Students' Learning Motivation in Oriental Food Processing Course during Online Learning Using Digital Smart Book Learning Media - Hidayati, Laili; Elmunsyah, Hakkun (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2021)
The learning process is conducted by interactively, inspirative, fun, and motivates the students with technology in order to improve students' motivation and learning outcomes. Then, this research aimed to improve students' learning motivation in Oriental Food Processing during online learning using digital smart book learning media. The subjects in this study were the 4th-semester students of Culinary Art Education Study Program, Industrial Technology, Faculty of Engineering, State University of Malang. The analysis used descriptive analysis. The data was collected using questioner through a Google form. Results showed that around ninety students were motivated to follow online learning using digital smart book media. Thus, it exhibited that the digital smart book learning media helped improve students learning motivation. The conclusion, this technology could be used for other courses as an innovative solution to overcome students' problems and difficulties in the online learning process.